2017
DOI: 10.2147/ott.s148772
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of CXCL5 in non-small cell lung cancer

Abstract: As a CXC-type chemokine, ENA78/CXCL5 is an important attractant for granulocytes by binding to its receptor CXCR2. Recent studies proved that CXCL5/CXCR2 axis plays an oncogenic role in many human cancers. However, the exact clinical significance of CXCL5 in lung cancer has not been well defined. Here, we found that the serum protein expression of CXCL5 was significantly increased in non-small cell lung cancer (NSCLC) compared with that in healthy volunteers. Immunohistochemistry staining revealed that CXCL5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 59 publications
(37 reference statements)
1
26
2
Order By: Relevance
“…As a confirmation, immunofluorescent staining and IHC showed increased CXCL5 expression in CAFs. In addition, it was demonstrated that nonsmall cell lung cancer, melanoma and CRC tumor cell lines also highly expressed CXCL5 which mold tumor microenvironment . Therefore, it seemed that CXCL5 was with diverse origins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a confirmation, immunofluorescent staining and IHC showed increased CXCL5 expression in CAFs. In addition, it was demonstrated that nonsmall cell lung cancer, melanoma and CRC tumor cell lines also highly expressed CXCL5 which mold tumor microenvironment . Therefore, it seemed that CXCL5 was with diverse origins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that nonsmall cell lung cancer, melanoma and CRC tumor cell lines also highly expressed CXCL5 which mold tumor microenvironment. 17,25,26 Therefore, it seemed that CXCL5 was with diverse origins. Taken together, these data indicated an intriguing effect of CXCL5 in melanoma and CRC tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has the clinical significance of CXCL5 in lung cancer been suggested. The serum level of CXCL5 is significantly elevated in patients with non-small cell lung carcinoma (NSCLC) and CXCL5 immunoreactivity is enhanced in lung cancer tissue (53). Furthermore, CXCL5 expression correlates with the histologic grade, tumor size, lymph node metastasis, overall survival, and progression-free survival in patients with NSCLC (53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned inflammatory markers, there were other candidate genes for which there was enhanced expression in the TNFα array in rHypoE‐7 neurones (Figure A). Many up‐regulated genes are part of the C‐X‐X motif ligand family, including Cxcl1, Cxcl2 and Cxcl5, which are chemokines involved in inflammasome activation and recruitment of immune cells . Cx3 cl1, also known as fractalkine, is induced in the hypothalamic neurones of diet‐induced obese mice, and was shown to have a role in hypothalamic inflammation and diet‐induced glucose intolerance .…”
Section: Discussionmentioning
confidence: 99%
“…Many upregulated genes are part of the C-X-X motif ligand family, including Cxcl1, Cxcl2 and Cxcl5, which are chemokines involved in inflammasome activation and recruitment of immune cells. 53,54 Cx3 cl1, also known as fractalkine, is induced in the hypothalamic neurones of diet-induced obese mice, and was shown to have a role in hypothalamic inflammation and diet-induced glucose intolerance. 55 Toll-interacting protein (Tollip) is another factor induced by TNFα in rHypoE-7 neurones.…”
Section: Discussionmentioning
confidence: 99%